A Deflationist Error Theory of Properties. (March 2015) - Båve, Arvid
Abstract I here defend a theory consisting of four claims about 'property' and properties, and argue that they form a coherent whole that can solve various serious problems. The claims are: (1) 'property' is defined by the principles (PR): 'F‐ness/Being F/etc. is a property of x iff F(x)' and (PA): 'F‐ness/Being F/etc. is a property'; (2) the function of 'property' is to increase the expressive power of English, roughly by mimicking quantification into predicate position; (3) property talk should be understood at face value: apparent commitments are real and our apparently literal use of 'property' is really literal; (4) there are no properties. In virtue of (1)–(2), this is a deflationist theory and in virtue of (3)–(4), it is an error theory. (1) is fleshed out as a claim about understanding conditions, and it is argued at length, and by going through a number of examples, that it satisfies a crucial constraint on meaning claims: all facts about 'property' can be explained, together with auxiliary facts, on its basis. Once claim (2) has been expanded upon, I argue that the combination of (1)–(3) provides the means for handling several problems: (i) they help giving a happy‐face solution to what I call the paradox of abstraction (basically that 'x has the property of being F' and 'x is F' seem equivalent yet different in ontological commitments), (ii) they form part of a plausible account of the correctness of committive sentences, and, most importantly, (iii) they help respond to various indispensability arguments against nominalism.